Anion vacancy correlated photocatalytic CO2 to CO conversion over quantum-confined CdS nanorods under visible light. Issue 8 (8th February 2023) - Guo, Qing; Xia, Shu-Guang; Xin, Zhi-Kun; Wang, Yang; Liang, Fei; Nan, Xiao-Lei; Lin, Zhe-Shuai; Li, Xu-Bing; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : In terms of electronic structure change, surface anion vacancies in II–VI semiconductors could promote CO generation rates, which have been confirmed as active sites for photocatalytic CO2 reduction. Abstract : Surface vacancies in II–VI semiconductors have been confirmed as active sites for photocatalytic CO2 reduction. Here we take quantum-confined CdS nanorod as a model photocatalyst to correlate anion vacancies with photocatalytic CO2 reduction performance. In terms of electronic structure change, CdS nanorods with more surface S vacancies give enhanced CO generation rates, which were confirmed by deliberately introducing S vacancies via a post-treatment.